Total Quality Management in Education - Thapa, Tara Bahadur (Academic Voices: A Multidisciplinary Journal, 2011)
Total Quality Management (TQM) is the latest in a parade of models, recipes, programs, frameworks, and slogans for guiding academic reform. It provides a tool to help ensure this quality. The management in TQM means everyone is the manager of their own responsibilities because everyone in the institution, whatever their status, position or role is. Information and technologies have brought sea changes in education and has therefore changed the interpretation of the term quality. TQM advocates that everything and everybody in the organization is involved in the academic institutions for continuous improvement. As it is applied to education, TQM faces new challenges due to diversity in nature of students and educators, large and multileveled classrooms, technological advances and new paradigms in educational content and delivery. Despite these issues education must maintain quality across classrooms, schools and institution. This article highlights the need of TQM to improve overall quality of education in Nepal. Keywords Total Quality Management, managerialism, educational management, quality improvement, application DOI: http://dx.doi.org/10.3126/av.v1i0.5314 Academic Voices 2011; 1: 80-83